Rancang Bangun dan Pengujian Mesin Pelumat Tanah Liat Bakal Cetak Batu Bata Metode Screw Conveyor - Delffika Canra; Dedi Suwandi; Afan Da’ud; Suliono; Meri Rahmi (Journal of Applied Mechanical Technology, 2022)
The clay crushing machine will print bricks to soften or thin the soil mixture after immersion in a pond. This machine can increase brick farmers' time efficiency and production in micro, small and medium enterprises (UMKM). The method used to soften or thin the dough is using a screw conveyor as a soil pusher and a crushing knife as a soil crusher. The results of processing clay using a crushing machine are smooth and even. The trial results that have been printed, then dried and burned, produce solid and good-quality bricks. This machine can pulverize quickly compared to traditional processors, and this machine can cut processing time by two days compared to the manual method. A crushing machine with a capacity of 3 kg, a trial process was carried out using four buckets of clay, then the capacity of the soil crushing process was around 3 kg per 5 seconds, with a capacity of 300 cm3/second. The calculation of the potential production potential of this crushing machine in 1 working day, which is 8 hours, is capable of processing clay that is ready for production as raw material for bricks up to 8640 bricks/per day